THE ROLE OF NATURE PROTECTION ACTIVITIES IN THE FORMATION ENVIRONMENTAL AWARENESS OF HIGH SCHOOL STUDENTS - Krasnoshtan, I. (SWorld-Ger Conference proceedings, 2023)
The article summarizes the education of students in environmental awareness, which is formed through environmental protection activities. In solving these problems, the leading role belongs to higher education, where in the cycle of natural and scientific